TINGKAT KEBERHASILAN SISTEM AGROFORESTRI DI DESA RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR - Faridatul Hasanah, Riska; Ervayenri, Ervayenri; Insusanty, Enny (Wahana Forestra: Jurnal Kehutanan, 2019)
This study aims to measure the success rate of the Agroforestry System in Rumbio Village. This research was conducted for 2 (two) months in April s.d. June 2019. Tools and materials used in the study were chest boards, label papers, questionnaires, interview guides, tally sheets, GPS, cameras, guards, phi bands, gauges, compasses, and plastic straps. While the objects studied were rubber plants, agarwood plants, and honey bee cultivation. Data collected in this study are primary and secondary data. Data collection methods used are (1) survey method with sampling techniques for measuring rubber and aloes plants; (2) filling out questionnaires and census interviews for honey bee cultivation. The results showed the success rate of kaet plants was around 53% and agarwood plants were 28%, this was due to several factors such as floods that occurred in 2017, lack of assistance, lack of plant maintenance, and for aloes plants there was no shade at the beginning of planting. As for the cultivation of honey bees, the results of this study indicate that the cultivation of honey bees is beneficial.